Optimal Cutoff Value of 1-Hour Postload Glucose to Identify Insulin Resistance in Women with Polycystic Ovary Syndrome - Sungwook Chun; Sihoon Lee (IMR Press, 2022)
Background: Despite the active researches recently conducted into the relationship between 1-h postload glucose (1-h PG) during standard oral glucose tolerance test and future risk of type 2 diabetes, research regarding the clinical capacity of 1-h PG to assess insulin resistance in those with polycystic ovary syndrome (PCOS) is still insufficient. The purpose of this study was to investigate the optimal 1-h PG cutoff value to identify insulin resistance in women with PCOS. Methods: One hundred fifty-three women aged 18 to 35 years who were diagnosed with PCOS were enrolled in this study. Insulin resistance was defined as having abnormal insulin sensitivity or hyperglycemia. Spearman's rank correlation coefficient and receiver operating characteristic (ROC) curve analyses were conducted to assess the relationship between 1-h PG and other parameters and to determine the optimal 1-h PG cutoff for identifying insulin resistance, respectively. Results: Significant correlations were observed between 1-h PG, 2-h PG and fasting glucose, and other fasting-state insulin sensitivity assessment indices, other than fasting insulin level. The optimal 1-h PG threshold value for identifying insulin resistance was 138.5 mg/dL. Categorization of patients based on the 1-h PG threshold showed significant differences for all laboratory variables related to insulin sensitivity/resistance, other than fasting insulin. Conclusions: Our results suggest that a 1-h PG value of ≥138.5 mg/dL may be a promising assessment index for identifying insulin resistance in women with PCOS.